Changing aetiology, clinical features, antimicrobial resistance, and outcomes of bloodstream infection in neutropenic cancer patients. (24th April 2012) - Gudiol, C.; Bodro, M.; Simonetti, A.; Tubau, F.; González‐Barca, E.; Cisnal, M.; Domingo‐Domenech, E.; Jiménez, L.; Carratalà, J.
Abstract Recent changes in the management of patients with haematological malignancies might have influenced the aetiology, characteristics, antimicrobial resistance and outcomes of bloodstream infection (BSI) during neutropenia. We compared 272 episodes of BSI in adult neutropenic patients with cancer prospectively collected from January 1991 to December 1996 (first period), when quinolone prophylaxis was used, with 283 episodes recorded from January 2006 to March 2010 (second period), when antibacterial prophylaxis was stopped. Patients in the second period were significantly older and were more likely to have graft‐versus‐host disease and a urinary catheter in place, whereas the presence of a central venous catheter, parenteral nutrition, corticosteroids and antifungal and quinolone prophylaxis, were more frequent in the first period. More patients in the first period had mucositis and soft‐tissue infection as the origin of BSI, but an endogenous source was more common during the second. Gram‐positive BSI was more frequent in the first period (64% versus 41%; p <0.001), mainly due to coagulase‐negative staphylococci and viridans group streptococci. In the second period gram‐negative BSI increased (28% versus 49%; p <0.001), quinolone susceptibilities were recovered, but multidrug‐resistant gram‐negative BSI also increased (1% versus 6%; p <0.001). Although patients in the second period were more likely to need admission to the intensive‐care unit, overall case‐fatality rate was similar in the two periods (19% versus 15%). The aetiology of BSI in neutropenic patients with cancer has shifted from gram‐positive to gram‐negative organisms. Multidrug resistance among gram‐negative bacilli is emerging as a therapeutic challenge. Overall case‐fatality rate remains high.